Kinetics of expression of infectious ecotropic, xenotropic, and mink cell focus-forming murine leukemia virus after 5-iododeoxyuridine induction of cells from high- and low-leukemia mouse strains. - Rapp, U R (1983)
Endogenous murine leukemia virus (MuLV) was induced with 5-iododeoxyuridine (IdUrd) from the high-leukemia mouse strain AKR and from two low-leukemia strains, C3H/He and BALB/c. A virus-free cell line from strain AKR readily gave rise to infectious, XC-positive MuLV upon treatment with IdUrd, whereas cells from strains C3H/He and BALB/c produced replication-deficient, XC-negative MuLV. IdUrd-induced cells also produced xenotropic and mink cell focus-forming MuLV. Xenotropic virus emerged at a higher titer from both AKR and BALB/c cells during two discrete time intervals, first at day 3 after induction and a second time during spread of the induced ecotropic MuLV. Xenotropic and mink cell focus-forming MuLVs were also produced by IdUrd-induced C3H/He cells but required another round of infection in Sc-1 cells for detection. The in vitro infectivity of endogenous ecotropic MuLV isolated by IdUrd induction from C3H/He cells correlated with pathogenicity in the Fv-1-compatible, leukemia-negative mouse strain NFS/N. Thus, the virulence of endogenous ecotropic MuLV may be an important factor in determining the leukemia incidence in these inbred strains of mice.